Rhinosporidioma: Primary Cutaneous Rhinosporidiosis - A Rare Case Report (Indian Journal of Case Reports, 2016)
Rhinosporidiosis is a chronic granulomatous disease caused by Rhinosporidium seeberi. Rhinosporidium seeberi causes granulomatous inflammation of mucocutaneous sites, presenting most frequently as polypoidal lesions in the nose. Sites like the conjunctiva, trachea, nasopharnyx, skin, and genitourinary tract are less frequently involved. Primary cutaneous lesion is extremely rare and it is often mistaken for soft-tissue tumour. We present a case of 55 years male patient from Thanjavur, Tamilnadu, with primary cutaneous rhinosporidiosis without mucosal involvement.